MR dokumentované vymizení infiltrate infundibula hypofýzy u pacientů s histiocytózou z Langerhansových bunek po lécbe 2-chlorodeoxyadenosinem - Vanícek, J; Adam, Z; Balsíková, K; Krejcí, M; Pour, L; Szturz, P; Zahradová, L; Hájek, R; Koukalová, R; Rehák, Z; Král, Z; Mayer, J (Vnitrni lekarstvi, 2011)
In adult patients, Langerhans cell histiocytosis (LCH) manifests most frequently with one or more osteolytic lesions or, alternatively, with pulmonary involvement with nodules and cysts or with skin lesions. Infiltration ofthe central nervous system is a rather rare sign of LCH. The LCH cells have an unexplained affinity to hypothalamus and to pituitary stalk and, consequently, central diabetes insipidus is the most frequent clinical sign of brain involvement in LCH. We describe treatment of 2 adult patients with LCH in whom central diabetes insipidus was the first sign of LCH and MR confirmed pituitary stalk infiltration. The first man was diagnosed with diabetes insipidus and pituitary stalk infiltration at 33 years of age. LCH was confirmed 2 years later by histology of verrucous lesions on the skin of perianal area. The disease affected the skin and CNS. The patient was treated with 2-chlorodeoxyadenosine (5 mg/m2 s.c. for 5 consecutive days of a 28-day cycle). No pituitary infiltration was evident on an MR image after the 4th cycle. Residual perianal infiltration was irradiated. The patient has been in complete remission for 44 months following treatment completion, although vasopressin and testosterone substitution is required. The second man was also diagnosed with diabetes insipidus and pituitary stalk infiltration at 33 years of age. Pulmonary involvement was identified with high resolution CT(HRCT) and high CD1a and S-100 positive elements with bronchoalveolar lavage. This patient further had external auditory canal infiltrations causing chronic discharge from the ears. The patient was treated with 2-chlorodeoxyadenosine as above. A follow up MR after the 4th cycle showed reduction in the infiltration diameter from 5.5 to 3.0 mm. Therefore, 2-chlorodeoxyadenosine 5 mg/m2 s.c. was combined with dexamethasone 20 mg p.o. during the 5th and 6th cycle. The MR image after treatment completion showed remission of the pituitary stalk infiltrate. External auditory canal infiltration diminished as did the nodules in pulmonary parenchyma. Nevertheless, vasopressin substitution is still required. The patient has been in complete remission for 8 months from the completion of the treatment. Pituitary stalk infiltration disappeared after the treatment with 2-chlorodeoxyadenosine in 2 patients; after 4 cycles in the first and after 6 cycles (with an addition of dexamethasone during the last 2 cycles) in the second.
Keywords: magnetická rezonanční tomografie; hypofýza; Cladribine; Pituitary Diseases; Pituitary Gland; Histiocytosis, Langerhans-Cell; Magnetic Resonance Imaging; mužské pohlaví; Diabetes Insipidus, Neurogenic; dospělí; Humans; kladribin; histiocytóza z Langerhansových buněk; Adult; Male; centrální diabetes insipidus; lidé; nemoci hypofýzy